2016
DOI: 10.1002/14651858.cd010571.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic duct guidewire placement for biliary cannulation for the prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis

Abstract: Pancreatic duct guidewire placement for biliary cannulation for the prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…This technique appears particularly helpful when cannulation is impeded by difficult anatomy, such as when there is a malignant biliary stricture or the ampulla is intradiverticular . Although those who use this technique frequently (author included) espouse its benefits, a recent Cochrane Collaboration review suggests that the double‐wire technique does not improve cannulation success but increases the risk of PEP compared to other techniques such as precut sphincterotomy and cannulation alongside a pancreatic stent . However, all component studies in this meta‐analysis were unblinded, the experience and comfort level of participating endoscopists with the double‐wire technique in these studies is unclear, and most included patients did not receive rectal NSAIDs or a prophylactic stent.…”
Section: Procedures Techniquementioning
confidence: 99%
“…This technique appears particularly helpful when cannulation is impeded by difficult anatomy, such as when there is a malignant biliary stricture or the ampulla is intradiverticular . Although those who use this technique frequently (author included) espouse its benefits, a recent Cochrane Collaboration review suggests that the double‐wire technique does not improve cannulation success but increases the risk of PEP compared to other techniques such as precut sphincterotomy and cannulation alongside a pancreatic stent . However, all component studies in this meta‐analysis were unblinded, the experience and comfort level of participating endoscopists with the double‐wire technique in these studies is unclear, and most included patients did not receive rectal NSAIDs or a prophylactic stent.…”
Section: Procedures Techniquementioning
confidence: 99%
“…Next, using a contrast medium under X-ray fluoroscopy, the catheter is inserted into the pancreatic bile duct. Interventional radiology procedures, such as ERCP, are often complex and involve long fluoroscopic analyses, resulting in significant radiation exposure to the operators [ 2 4 ]. Therefore, radiation protection for interventional radiology staff is an important issue [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that PGW technique was a risk factor on multivariate analysis. It is reported that PGW technique increased PEP in difficult cannulation cases . On the other hand, some studies suggested that PGW technique did not increase PEP .…”
Section: Discussionmentioning
confidence: 95%
“…It is reported that PGW technique increased PEP in difficult cannulation cases. 29,30 On the other hand, some studies suggested that PGW technique did not increase PEP. 31,32 However, SOD is excluded in the report of Xinopoulos et al 31 In the group limited to SOD there are few papers confirming that PGW technique is a risk for PEP.…”
Section: Discussionmentioning
confidence: 99%